Development of a web-based intervention to improve health screening uptake in men: The ScreenMen study / Teo Chin Hai - Teo, Chin Hai (2018)
Health screening has been shown to improve health outcomes and reduce mortality. However, its uptake remains unsatisfactory particularly in men and among those aged below 40 years old, which is a critical window period to detect and prevent diseases from progressing. High internet access and mobile phone ownership make ICT a potential solution to improve screening uptake among young men. This study therefore aims to describe the development of ScreenMen, a mobile web app to improve screening uptake in men based on theories, evidence and users’ needs. ScreenMen was developed in two phases. In the exploratory phase, a comprehensive framework was formed based on behavioural and masculinity theories, and literature review of barriers and facilitators to health screening in men. A list of evidence-based screening tests was identified using international and local clinical guidelines. A needs assessment was also conducted with men from a banking institution in Kuala Lumpur to explore their needs when undergoing health screening. In the development phase, findings from the exploratory phase were synthesized to form the content of ScreenMen. ScreenMen was developed using an iterative approach involving testing with experts and users for its utility and usability. The prototype was first tested with experts using prospective think aloud method. The revised prototype was then tested with men from the banking institution using retrospective think aloud method, and evaluated using System Usability Scale (SUS) and change in intention to screen. From the needs assessment with 31 men, misconceptions about screening, such as ‘screen only when sick’, were the key barriers to screening. Furthermore, men were unaware of their health risks and the screening tests they should go for. They also lacked knowledge about the cost, when and where to screen. ScreenMen addressed these barriers through three modules: health screening educational video, health assessment function iv and frequently asked questions. The final ScreenMen web is male-sensitive (e.g. using car maintenance analogy), interactive (providing personalised health advice), evidencebased and mobile-responsive. It also mimics a real-life clinical consultation by interacting with a virtual doctor. During the testing with the experts, the contents were found to be valid and up-to-date. The users found ScreenMen useful as they could learn more about their health and screening without consulting a doctor. However, some users wanted ScreenMen to be shorter; therefore a ‘Quick Assessment Mode’ was added and the information was reordered to address this need. In addition, the importance of avoiding unnecessary screening tests was further emphasised in the revised ScreenMen to advocate evidence-based screening. The preliminary evaluation found ScreenMen to be userfriendly with a mean SUS score of 76.4 (good usability range: 71.4-85.5). Eight out of 23 men wanted to attend screening earlier than intended after using the ScreenMen. Of 12 men who were in pre-contemplation stage, four changed to either contemplation or preparation stage. The ScreenMen has been developed systematically using a usercentred approach to empower men to undergo screening. The preliminary data suggest that ScreenMen is acceptable to men and might improve their intention to screen.